The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1365-2222.2009.03349.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased vascular permeability precedes cellular inflammation as asthma control deteriorates

Abstract: Our results suggest that airway vascular leakage is a major pathophysiologic feature of early asthma deterioration, occurring before recrudescence of cellular inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 54 publications
1
54
0
3
Order By: Relevance
“…Oedema would act to thicken the airway wall, therefore decreasing lumen size. Increased vascular permeability occurs as asthma control deteriorates [75]; however, oedema is not related to changes in AHR during allergen challenges [76]. This finding is supported by studies in animals that have found that oedema causes only modest airway narrowing [77].…”
Section: Do Respiratory Viral Infections Reduce B 2 -Agonist Efficacy?supporting
confidence: 74%
“…Oedema would act to thicken the airway wall, therefore decreasing lumen size. Increased vascular permeability occurs as asthma control deteriorates [75]; however, oedema is not related to changes in AHR during allergen challenges [76]. This finding is supported by studies in animals that have found that oedema causes only modest airway narrowing [77].…”
Section: Do Respiratory Viral Infections Reduce B 2 -Agonist Efficacy?supporting
confidence: 74%
“…Markers of vascular permeability; perivascular albumin staining and BALf microalbumin levels were also elevated in these asthmatic subjects on high-dose inhaled corticosteroid therapy compared to healthy controls and airway albumin levels correlated with infiltrating T lymphocytes. The proportion of airway vascularity (number and size of blood vessels) and VEGF levels in this cohort of asthmatic subjects was not altered when the dose of fluticasone propionate was halved and associated with clinical asthma deterioration yet without the return of cellular inflammation [81] suggesting that vascular leakage is a feature of asthma deterioration that may precede the return of cellular inflammation.…”
Section: Vascular Inflammation and Remodelling Processes In Asthmamentioning
confidence: 73%
“…We demonstrated that Nrf2 reduces airway leakiness in vivo. Both in vitro and in vivo studies have shown that the airway epithelium of individuals with asthma is leakier than in normal subjects (21,59). To further address the role of Nrf2 in barrier function, we performed ex vivo experiments using tracheal epithelial cells from Tam-Keap1 Ϫ/Ϫ and CC10-Keap1…”
Section: Discussionmentioning
confidence: 99%